Biomechanical compatibility study of a nickel-free medical TiNbZr shape memory alloy. Issue 1 (June 2021) - Nasakina, E O; Konushkin, S V; Sudarchikova, M A; Novikova, D A; Sergiyenko, K V; Kolmakova, A A; Mikhailova, A V; Shatova, L A; Kolmakov, A G; Sevostyanov, M A
Abstract: Biomechanical compatibility of a Ti-(20-30) Nb-5Zr shape memory alloy was studied. The tensile strength study was carried out. The best properties are observed for the Ti-28Nb-5Zr composition with a wire diameter of 1200 μm, adapted to work in a living organism. The dependence of the change in strength and plasticity on the annealing temperature exhibits minimal extrema. The best characteristics are noted at 800 °C.